Corporate Computer Crime: Collaborative Power in Numbers. - Wiggins, Lynne M. (Federal Probation, 2002)
Collaborative alliances are needed between corporations and law enforcement in order to prevent a parallel between corporate computer crime rates and the technological advances. When integrated into conventional white-collar crimes, high technology has created four categories of corporate computer crime: innocent hackers, computers as a tool, computers as a target, and computer-related crime. Methods for combating computer crime involve both the authorities and corporations, and both groups believe that their way of doing things is the correct way. However, each belief should be considered as part of the total solution to the problem, and combined, they could be used to create a greater wall of defense against computer crime offenders.